A Model of Supply Chain Finance - Bo Hu; Makoto Watanabe; Jun Zhang (Center for Economic Studies and ifo Institute (CESifo), 2023)
This article develops a model in which an intermediary uses a supply chain finance (SCF) program to fund suppliers. The SCF program pools liquidity from suppliers and meanwhile provides immediate payment to suppliers with pressing liquidity needs. We show that the intermediary optimally selects not only suppliers with positive profitability but also suppliers with negative profitability who, however, contribute to the liquidity pool. Inserting the model to an otherwise standard monetary framework, we show that with higher nominal interest rates, the SCF program emphasizes the liquidity contribution more and the profitability contribution less. Deviating from the Friedman rule, where only suppliers with positive profitability are selected, may lead to welfare gains.
Keywords: E41; E42; E51; G23; 330; supply chain finance; liquidity pooling; liquidity cross-subsidization; money search; intermediary